First discovery of Antarctic amber - Klages, Johann Philipp; Gerschel, Henny; Salzmann, Ulrich; Nehrke, Gernot; Müller, Juliane; Hillenbrand, Claus-Dieter; Bohaty, Steven M.; Bickert, Torsten (Antarctic science, 2024)
Here, we report the first discovery of Antarctic fossil resin (commonly referred to as amber) within a ~5 cm-thick lignite layer, which constitutes the top part of a ~3 m-long palynomorph-rich and root-bearing carbonaceous mudstone of mid-Cretaceous age (Klages et al. 2020). The sedimentary sequence (Fig. 1) was recovered by the MARUM-MeBo70 seafloor drill rig at Site PS104_20 (73.57° S, 107.09° W; 946 m water depth) from the mid-shelf section of Pine Island trough in the Amundsen Sea Embayment, West Antarctica, during RV Polarstern Expedition PS104 in early 2017 (Gohl 2017; Fig. 1a). So far, amber deposits have been described from every continent except Antarctica (Langenheim 2003, Quinney et al. 2015; Fig. 1a).